Current Application of Wastewater Quantity Estimation Method for Infrastructure Construction Projects of Industrial Zones in Vietnam - Khải, Nguyễn Mạnh (VNU Journal of Science: Earth and Environmental Sciences; Vol 33 No 1SDO - 10.25073/2588-1094/vnuees.4181, 2017)
According to the Law on Environmental Protection, the Environmental Impact Assessment (EIA) report must be approved for investment in the construction of industrial zone (IZ), in which the amount of wastewater discharged by the IZ needs to be estimated. The study was conducted to review 114 IZs EIA reports approved from 2006 to 2016 with an occupying rate of 80-100%. In order to estimate wastewater dischaged from IZ, four methods have been applied: (1) estimating the amount of wastewater corresponding to water demand based on the area of the IZ; (2) using the coefficient of wastewater based on the area of the IZ; (3) basing on the performances of previous periods and (4) unknown basis of calculation. The most common method is the first one applying TCXDVN 33:2006, accounting for 37.72% of the reports. RMSE of this method is 9,000m 3 /day which is the highest among four methods. The main cause for this difference is the exclusion of production features technical guidelines. Besides, there is no consideration of the coefficients of water supply and wastewater for non-industrial components such as warehouses, service areas, technical and administrative areas.